The Effects of Methanol Extract of Rue Leaves (Ruta graveolens) on Body Weight, Lipid Profile, Adipokine Levels, TCPTP, and Perilipin-1 Expression in Obesity Model Rats - Kusumaningrum, Sulistyani; Mudigdo, Ambar; Purwanto, Bambang; Indarto, Dono (Trends in Sciences, 2025)
Obesity is one of the non-communicable diseases that becomes a health problem with high prevalence every year. Rue leaves (Ruta graveolens) containing a rutacridone active compound can computationally interact with T cell protein tyrosine phosphatase (TCPTP) and have anti-obesity activity properties. Therefore, this study aimed to investigate the Methanol Extract of Rue Leaves (MERL) on Body Weight (BW), Obesity Index (OI), Subcutaneous Fat Thickness (SFT), lipid profile, Fasting Blood Glucose (FBG), Leptin (LEP) and Adiponectin (ADP) levels, TCPTP and Perilipin-1 expression in obesity model rats (OR). This study was an animal experiment with a pre-posttest control group design, which used 48 male rats of the Sprague-Dawley strain and was randomly divided into 6 groups. The normal Group (N) was male rats + rat standard feed (BR-2). The negative and positive Groups (NC and PC) were obese rats (ORs) + BR-2 + 1 mL of 0.9% NaCl and 0.6 mg/kg BW pure rutacridone, respectively. The treatment groups (T1-T3) were ORs + BR-2 + 80, 100, or 200 mg/kg BW MERL for 30 days. Our results demonstrated that MERL administration significantly reduced BW, OI, SFT, TG, TC, LDL-C, FBG, and LEP levels and significantly increased HDL-C and ADP levels with p ˂ 0.05, compared to the NC group in a dose-dependent manner. Our data also showed low expression of TCPTP and Perilipin-1 in all treatment groups. In conclusion, MERL administration reduces leptin, TG, TC, LDL-C, FBG levels, SFT, BW, and OI while increasing ADP and HDL-C levels in male obese rats. HIGHLIGHTS Methanol extract of Rue leaves (MERL) chemically contains Osthol, Psoralen, Rutin, Scoparone, and Quercetin, which potentially become anti-obesity agents. Measuring subcutaneous fat thickness (SFT) using an ultrasound sonography device provides accurate data for determining rat obesity. Administration of 100 mg/kg BW/day MERL effectively reduces leptin, triglyceride, total cholesterol, LDL-Cholesterol, fasting blood glucose levels, SFT, body weight, and obesity index while increasing adiponectin and HDL-Cholesterol levels in male obese rats. GRAPHICAL ABSTRACT